The problem of baby blues among Polish obstetricians - the scope of knowledge among medical students - Nawrocki, Maciej; Zwierzyńska, Anna; Wojciechowski, Piotr; Nowakowska, Ilona; Wasiak, Wojciech; Gruszka, Jakub; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2021)
Introduction Mental disorders are a common problem of women during the puerperium. Baby blues is an immediate emergency and a danger to the mother. It can develop into depression or postpartum psychosis. Hormonal changes related to the decrease in the level of estradiol, progesterone and prolactin after childbirth are considered to be the pathogenesis of this phenomenon. Postpartum depression is a self-limiting and transient disorder. However, it should not be taken lightly. The most important thing is to identify symptoms early and intervene. Aim of the study The aim of the study was to assess students’ knowledge of the baby blues phenomenon and the impact of factors such as place of residence or education on the state of knowledge. Material and methods 318 medical students of the Jan Kochanowski University were included in the research. The data was collected using the author’s questionnaire. The Bioethics Committee approved the study. Statistical analysis was performed with the use of the Statistica 13 computer program. Results and conclusions The highest percentage of the respondents is in the 20-30 age group. City dwellers constitute the most numerous group. The average level of the respondents’ knowledge about baby blues is 75%. The most frequently indicated sources of knowledge are the Internet and TV programs. It is important to make patients aware of how to choose a reliable source of information. Health education is crucial for future parents. It can result in a reduction in the level of stress associated with the new situation of having children.